Audience Acceptance of the 90s Generation Lifestyle in Bebas Films - Luthfiah Hikmah Sabella; Filosa Gita Sukmono (Jogjakarta Communication Conference (JCC), 2023)
This study uses the film Bebas to find out how the audience's reception of the 90s generation's lifestyle in Bebas films. The lifestyle of the 90s generation in the film is Bebas chosen because that is the main attraction in this film, even to the point where a concert titled 90s party is held ahead of the screening of this film. Nonetheless, there is some scene which is considered to create a negative impression for the 90s generation. This has attracted the interest of researchers to find out how the audience interprets the lifestyle of the 90s generation in Bebas films. In addition, there has been no research on Bebas films that focuses on studying audiences. The themes examined in this film are the fashion generation of the 90s, brawls and fights, and slang. This study uses reception analysis theory with a model encoding-decoding belonging to Stuart Hall with data collection techniques of interviews with six informants. The results of the study show that the meaning of each informant is different, namely dominant hegemony, negotiation, and opposition. This proves that the audience is active, because they do not always fully accept the messages conveyed by the media, but they also reinterpret the messages they receive, and the results depend on the background and experience of each informant.